Influence of supplemented genistein and daidzein on the production performance and egg structure during the first egg-laying cycle - GJorgovska, Natasha; Filev, Kiril; Grigorova, Svetlana (University Ss Ciril and Methodius in Skopje, Institute of Animal Science, 2019)
The process of egg formation and egg quality depend on several biomechanisms that can be modifed by various environmental, genetic and nutritional components. This experiment was performed to estimate the influence of supplementation with dietary isoflavones (daidzein and genistein) in feed on the production performance and egg structure during the first egg production period. Eighty ISA Brown laying hens were randomly divided into four groups, 20 birds per group, and surveyed during 3 consecutive periods (27–42 wks, 43–60 wks and over 60 wks). Concerning diet supplemented with isoflavones (genistein and daidzein), the egg weight was statistically different compared with the control group (confidence interval of 95%) in all the 3 periods of the experiment. The yolk:white ratio was signifi-cantly higher in the control group compared with the groups fed with 1000, 2000 and 3000 mg of isoflavones per 1 kg of feed in the periods of 27–42 wks and 43–60 wks (P<0.05).
Keywords: soy isoflavones; laying hens; egg structure